Mathematical Computational Thinking Skills In The Context of Critical Thinking Based On Gender - Lestari, Nur Alimah Agung; Alyani, Fitri (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Computational thinking is related to critical thinking skills. The purpose of this research is to find out how students' ability in mathematical computational thinking in the context of critical thinking and the differences in the abilities of women and men. This research is a qualitative research. Data collection techniques used written tests, interviews, and documentation. The subjects of this study were selected through purposive sampling technique and totaled 34 students. After that they did a written test with 7 questions on the material of the system of linear equations of two variables and obtained 6 students with the category of 2 high ability students, 2 medium ability students, and 2 low ability students. The data were analyzed by using Triangulation technique. The results showed that female students are superior in solving problems according to the indicators of computational thinking because they pay more attention to accuracy in the work. So it must often work on problems to train students' abilities so that all students can do it better and become balanced for each student's ability. So it is hoped that students will get used to thinking in a stepped, systematic and logical manner.